Poprawa sytuacji finansowej rolników po przystąpieniu do grup producentów rolnych - Lemanowicz, Marzena (Product Quality Improvement Process - a More Efficient System of Customer's Needs and Expectations Satisfaction in Agribusiness Enterprises, 2005)
The paper presents partial results of the research that was carried within agri-producer groups in Poland. There were presented profits gained by farmers thanks to the group cooperation. The main part of the paper states an econometric model in which several factors improving farmers' financial situation after accession to the groups are shown. Moreover, the author's attention is paid to the legal acts that have been regulating the groups' activity in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 15-20